Adsorptive Dephenolization of Aqueous Solutions Using Thermally Modified Corn Cob: Mechanisms, Point of Zero Charge, and Isosteric Heat Studies - Ositadinma Chamberlain Iheanacho; Joseph Tagbo Nwabanne; Christopher Chiedozie Obi; Chinenye Adaobi Igwegbe; Chijioke Elijah Onu; Irvan Dahlan (Adsorption Science & Technology)
The sorption mechanisms, point of zero charge, and isosteric heats involved in the adsorptive dephenolization of aqueous solutions using thermally modified corn cob (TMCC) were studied at different initial phenol concentrations (100–500 mg/l), TMCC dosage (0.4–2.0 g), contact time (5–60 min), pH (2–10), and temperature (30–60°C). Analysis of the adsorbent material showed that it possessed the properties typical of a good adsorbent. The adsorption experiments revealed that phenol uptake is favored by an increase in TMCC dosage and contact time and a decrease in temperature and concentration of phenol in the solution. The experimental data were well-fitted to the Sips, Langmuir, Toth, and Redlich–Peterson isotherm models. Thermodynamic studies suggested that the sorption of phenol onto TMCC is feasible, spontaneous, and endothermic. The isosteric heats of adsorption obtained are in the range 47.43-79.38 kJ/mol, confirming that the adsorption process is predominantly a physical process depicting the van der Waals interactions, and it is inversely proportional to surface loading. The analysis of the adsorption mechanisms showed that the intraparticle, film, and pore diffusion mechanisms were significantly involved in the phenol adsorption process. The involvement of electrostatic attraction, π‐π electron-donor interaction, and hydrogen bonding was also demonstrated. The point of zero charge (pHpzc) was obtained at a pH of 5.83; being slightly lower than the optimum pH of 6 indicates that the sorbent surface is obviously not negatively charged at pHpzc. The discoveries of this study have shown that the dephenolization process is feasible, spontaneous, endothermic, dominated by a physical process, and governed by intraparticle, film, and pore diffusion mechanisms.